The Youth Olympic Games: a facilitator or barrier of the high-performance sport development pathway?. Issue 1 (1st January 2018) - Kristiansen, Elsa; MacIntosh, Eric W.; Parent, Milena M.; Houlihan, Barrie
ABSTRACT: Research question: This paper examined the impact of participation in YOG on Norwegian team members with a particular emphasis on differences between those who continued in elite sport and those that dropped out. Research methods: We used a retrospective survey design to collect quantitative and qualitative data from former Norwegian YOG participants (from 2010, 2012, and 2014), with 58 of the 64 athletes responding to the survey in December 2015. Results and findings: Ericsson, Krampe, and Tesch-Roemer's [(1993). The role of deliberate practice in the acquisition of expert performance. Psychological Review, 100 (3), 363–406] typology of constraints and their concept of deliberative practice provided the framework for the data analysis. Key findings include: (a) the dropout rate was lower than that reported for similar groups; (b) the main reasons for dropout were school pressures and poor relations with the coach; (c) there was little difference in the perceived level of support from schools, parents and coaches between those who dropped out and those who did not; (d) participation in the YOG was a significant motivating factor for staying in elite-level sport for some athletes; (e) medal winners were as likely to dropout as non-medal winners; and (f) the national context for elite youth development may play a larger role in deeper engagement in sport than YOG participation. We derive hypotheses/propositions based on our results, which should be tested in future studies. Implications : Our findings suggest the entourage's support is critical for continued engagement in sport, but is not sufficient for preventing dropout. The national context, in terms of the sport and education systems, must align to ensure young athletes do not need to choose between elite-level sport and school. The national context may play a larger role in deeper engagement in sport than YOG participation/success.